A vestimenta e a moda: uma análise da revista estilo - Nunes, Gilcerlandia Pinheiro A. (2010)
This research addresses the consumption of women's fashion, through an analysis of the contents of the Estilo magazine. This magazine is an licensing of American Instyle, directed at the female, published by Editora Abril in Brazil since 2002. To guide this research, in relation of the fashionable field, some relevants concepts and authors were worked, like Pierre Bourdieu, Gilda de Souza Melo, Georg Simmel, Gilles Lipovetsky among other fundamental to understanding both the consumption and fashion. Still in search of understanding the discourses that permeated the fashion world were done semi-structured interviews with two costume designers who work in two different shops specializing in fabrics in the Natal's city. Were analyzed Estilo magazines published from June 2008 to June 2009, relating to the data collected in interviews in order to understand how discourses are constructed and disseminated, becoming so efficient in the seduction of women's groups which is directed to achieve and consolidate the production of appropriate and acceptable form to wear